Frequency of transverse vibration of regular polygonal plates with a concentric, circular orthotropic patch - Gutierrez, Ruben Hector (2000)
A first order approximation treatment of the case where a repair is made of the central portion of a vibrating isotropic plate of regular polygonal shape using a material of circularly anisotropic constitutive characteristics is presented. The mathematical model is also valid in the case of a vibrating isotropic plate where the central core has been damaged and it is assumed that this subdomain of the plate acquires polarly orthotropic properties.